The determinant of air pollution in Malaysia / Mizi Ibrahim Rosli - Rosli, Mizi Ibrahim (2019)
This purpose of studies is to investigated the relationship between selected economic indicator with air pollution which is significant or insignificant in Malaysia with period of 30 years from 1985 to 2014. This study using time series of data with selected and suitable method of estimations. Based on the result, all variables that been used have and positive and significant relationship between manufacturing, urban population, and agriculture with air pollution in Malaysia by using suitable data analysis and data regression.